2019
DOI: 10.1186/s13048-019-0492-6
|View full text |Cite
|
Sign up to set email alerts
|

TOP2A as marker of response to pegylated lyposomal doxorubicin (PLD) in epithelial ovarian cancers

Abstract: ObjectiveRelapsed epithelial ovarian cancer (EOC) is frequently treated with pegylated liposomal doxorubicin (PLD). Unfortunately, most patients do not benefit from treatment. Prediction of response is crucial to optimize PLD use and avoid unnecessary toxicities. We aimed at assessing the value of topoisomerase II alpha (TOP2A) expression as predictive marker of response to PLD-based therapy in patients with relapsed EOCs.MethodsWe retrospectively analyzed Formalin Fixed Paraffin Embedded (FFPE) tissues from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Topoisomerase II alpha (TOP2A), a potential biomarker for cancer therapy, has been detected in various types of cancer. 80 82 It participates in chromosome condensation and chromatid separation. 80 TOP2A encodes topoisomerase II alpha 81 and is reported to be overexpressed in HCC tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Topoisomerase II alpha (TOP2A), a potential biomarker for cancer therapy, has been detected in various types of cancer. 80 82 It participates in chromosome condensation and chromatid separation. 80 TOP2A encodes topoisomerase II alpha 81 and is reported to be overexpressed in HCC tissues.…”
Section: Discussionmentioning
confidence: 99%
“… 80 82 It participates in chromosome condensation and chromatid separation. 80 TOP2A encodes topoisomerase II alpha 81 and is reported to be overexpressed in HCC tissues. 83 Furthermore, a study has shown that TOP2A has prognostic value in HCC and its reactive agents can be used in HCC therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, TOPA2 encodes a DNA topoisomerase, an enzyme which releases torsional tension of the DNA duplex during transcription and replication [30]. A recent study shows that patients' tumors overexpressing TOPA2 might be more responsive to pegylated liposomal doxorubicin in platinum resistant ovarian cancer [31].…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme encoded by this gene coordinates chromosomal condensation processes and chromatid formation and relieves any mechanical strains occurring during transcription and DNA replication. TOP2A can play an important prognostic role in epithelial ovarian cancer (EOC) [38]. It has also been indicated that TOP2A overexpression occurs in ovarian tumors: it is currently the main target of clinical trials of ovarian cancer therapies [39].…”
Section: Discussionmentioning
confidence: 99%